”Byens bedste brugte bøger”: Bogen som vare og samlerobjekt i nye eksperimenterende romaner - Tanderup, Sara (K&K - Kultur og Klasse, 2017)
Literary culture has recently become aware of the book. The spread of new media results in a situation, where the printed book can no longer be taken for granted. The article investigates how the changing cultural and commercial status of the book is reflected in two new experimental novels, Mette Hegnhøj’s Ella er mit navn vil du købe det? (2014) and J.J. Abrams and Doug Dorst’s S. (2013). Drawing on theoretical perspectives of e.g. Jessica Pressman, Dominik Schrey and Henry Jenkins, I investigate how these works celebrate the book as an auratic object and as a privileged old medium – while also presenting and marketing the book as a commodity, that currently acquires new commercial value exactly because it can no longer be taken for granted. Thus, I argue that the two works in different ways reflect the new ambiguous status of the printed book: it is celebrated as a guarantor of a traditional literary culture and thus positioned in opposition to the contemporary commercialized media culture – while also being (as it always has been) a commodity and thus functioning on the commercial and cultural conditions of this new media culture.